FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU PEMILIH DALAM PILKADA KABUPATEN MANGGARAI TAHUN 2020 (STUDI PERBANDINGAN SUARA DI KELURAHAN BARU, KELURAHAN REO, KELURAHAN MATA AIR, KELURAHAN WANGKUNG KECAMATAN REOK, KABUPATEN MANGGARAI, PROVINSI NUSA TENGGARA TIM - Pena, Veronika Ruba; Niron, Eusabius Separera; Bidi, Maximianus Ardon (JURNAL EDUCATION AND DEVELOPMENT, 2025)
This study aims to analyze the changing behavior of people's voting and the factors that influence changes in people's behavior in four sub-districts. The research methodology uses a qualitative approach through descriptive analysis, namely collecting data from informants through direct interviews. The results of the study show that changes in people's behavior occur due to factors such as vision and mission, track record, and the influence of the candidate's work experience, while social background factors have no effect. The conclusion of this thesis is that there are three factors that influence changes in people's behavior in four sub-districts, namely vision and mission, track record, and the influence of the candidate's work experience, while social background factors have no effect in the four sub-districts. This is due to the factor of distrust and community boredom with the incumbent or candidate pair number 1 who are running again in the 2020 regional elections being the main factors that can influence people's choices, especially people in the four sub-districts in Reok District.